Methodological basis of assessing educational results of student choreographers in the context of classic dance study - Altukhov, Vadym; Pokrovska, Olena (Professional Art Education, 2025)
Purpose of the study. The article highlights the theoretical foundations and practical approaches to methodological assessment of knowledge and professional competencies of students specializing in B6.03 «Choreographic Art», using classical dance as an example. The focus is on aligning traditional teaching methods with the modern requirements of competence-based education, which involves the integration of innovative technologies, interdisciplinary components, and objective diagnostic criteria.Methods & methodology. The research methodology is based on competence-oriented and interdisciplinary approaches. Theoretical methods (analysis, synthesis, content analysis) were applied to study sources and define assessment criteria; empirical methods (pedagogical observation, analysis of academic and performance works, expert evaluation) were used to determine students’ level of preparedness; and modeling was employed to develop the structure of criteria and indicators.Scientific. The scientific novelty lies in the systematization of criteria, indicators, and levels of assessment in accordance with the structure of professional competence of the performer. The content of cognitive, technological, artistic-imagery, and psychophysical components was clarified as the basis for evaluating learning outcomes. A model was proposed to enhance the validity and objectivity of pedagogical diagnostics in performance disciplines. Results. The results made it possible to define the structure of students’ professional readiness, which includes motivational orientation, theoretical awareness, mastery of anatomical and physiological foundations of movement, and practical performance skills. The importance of developing reflective abilities for self-assessment and performance correction was established. The necessity of integrating interdisciplinary components (dance pedagogy, anatomy, musicality) and practice-oriented forms of training – open lessons, creative performances, expert evaluation –was substantiated. Educational modules on classical dance technique and methodology were analyzed, including structured exercises, movement combinations, training in musical-rhythmic coordination, and psychophysical preparation. Effective methods were identified as technical-lexical exercises, improvisational techniques, biomechanical complexes, and digital video analysis tools. Conclusions. The systemic methodological approach has been proven as an effective tool for objective assessment of knowledge and competencies of students specializing in B6.03. The structure of future choreographers’ readiness was generalized (motivational, cognitive, technical-performance, artistic-imagery, and reflective components). The practical significance lies in the standardization of educational modules, improvement of criteria, and implementation of unified approaches to certification.
Keywords: choreographic pedagogy; classical dance; methodological approach; professional competence; traditions and innovations; performance mastery; learning outcomes assessment; evaluation criteria; systematization of assessment methods